The mere sight of loved ones does not inhibit psychophysiological defense mechanisms when threatened - Bublatzky, Florian; Schellhaas, Sabine; Guerra, Pedro (Scientific reports, 2022)
Looking at pictures of loved ones, such as one's romantic partner or good friends, has been shown to alleviate the experience of pain and reduce defensive reactions. However, little is known about such modulatory effects on threat and safety learning and the psychophysiological processes involved. Here, we explored the hypothesis that beloved faces serve as implicit safety cues and attenuate the expression of fear responses and/or accelerate extinction learning in a threatening context. Thirty-two participants viewed pictures of their loved ones (romantic partner, parents, and best friend) as well as of unknown individuals within contextual background colors indicating threat-of-shock or safety. Focusing on the extinction of non-reinforced threat associations (no shocks were given), the experiment was repeated on two more test days while the defensive startle-EMG, SCR, and threat ratings were obtained. Results confirmed pronounced defensive responding to instructed threat-of-shock relative to safety context (e.g., threat-enhanced startle reflex and SCR). Moreover, threat-potentiated startle response slowly declined across test days indicating passive extinction learning in the absence of shocks. Importantly, neither a main effect of face category (loved vs. unknown) nor a significant interaction with threat/safety instructions was observed. Thus, a long-term learning history of beneficial relations (e.g., with supportive parents) did not interfere with verbal threat learning and aversive apprehensions. These findings reflect the effects of worries and apprehensions that persist despite the repeated experience of safety and the pictorial presence of loved ones. How to counter such aversive expectations is key to changing mal-adaptive behaviors (e.g., avoidance or stockpiling), biased risk perceptions, and stereotypes.